Nutritional supplement for athletic performance: Based on Australian Institute of Sport Sports supplement framework - Kim, J. (Exercise Science, 2019)
INTRODUCTION: Many athletes use nutritional supplements for their performance enhancements and training effects. However, it is unclear that some of the dietary supplements have favorable outcomes, and others may increase the risk of doping or side effects. METHODS: In this review, we discuss the Australian Institute of Sport (AIS) Sports Supplement Framework`s Group A performance supplements regarding safety, legality, and effectiveness in improving sports performance. Group A supplements include caffeine, beta-alanine, bicarbonate, beetroot juice, creatine, and glycerol. RESULTS: We found the use of these performance supplements could help athletes improve strength and endurance. However, the effects vary with individual athletes and depend on sports characteristics, training content, physical condition, and habits. CONCLUSIONS: Therefore, a case-by-case approach is warranted to ensure their desirable effects. It is important to consult a doctor or sports nutritionist before consuming theses supplements and to monitor the individual`s response through simulation.